Patterns and determinants of modern contraceptive use and intention to usecontraceptives among Malawian women of reproductive ages (15-49 years) - James Forty; Serai Daniel Rakgoasi; Mpho Keetile (BMC, 2021)
Abstract Background Malawi is one of the countries in SSA with the highest TFR. This study aimed to explore factors associated with modern contraceptive use and intention to use contraceptives among women of reproductive ages (15-49 years) in Malawi. Methods The study used secondary data from 2015 to 16 Malawi Demographic and Health Survey (MDHS) dataset. Logistic regression models were used to derive adjusted odd ratios as the measures of association between need, predisposing and enabling factors, and contraceptive use and the intention to use contraceptives among women. The sample constituted 24,562 women who were successfully interviewed during the MDHS. All comparisons are considered statistically significant at 5% level. Results Overall 54.8% of women were currently using contraceptives, while 69.1% had the intention to use contraceptives. The odds of contraceptive use were significantly low among, women aged 15-19 years, 20-24 years, 25-29 years, 30-34 years, 35-39 years and 40-44 years compared to women aged 45-49 years; women of Tonga ethnic group (OR = O.60, CI = 0.43 0.84) compared to women of Nyanga ethnic group; women from poor households (OR = 0.78, CI = 0.68-0.90) and middle income households (OR = 0.84, CI = 0.74-0.95) compared to women from rich household. Nonetheless, women with no past experience of terminated pregnancy (OR = 1.50, CI = 1.34-1.68) were more likely to use contraceptives compared to women with past experience of terminated pregnancy. Similarly, Women with primary education (OR = 1.56, CI = 1.16-2.09) and secondary education (OR = 1.39, CI = 1.04-1.85) were more likely to use contraceptives compared to women with higher education. While the odds of intending to use contraceptives were significantly high with age only thus among women aged 15-19 years, (OR = 15.18, CI = 5.94-38.77); 20-24 years (OR = 16.77, CI = 7.46-37.71); 25-29 years (OR = 6.75, CI = 3.16-14.45); 30-34 years (OR = 7.75, CI = 3.61-16.65) and 35-39 years (OR = 5.05, CI = 2.29-11.12) compared to women aged 45-49 years. Conclusion As direct policy measure; information, education and communication programmes on family planning among poor and middle income women, and all women in reproductive ages should be strengthened.